Resection of inverted papilloma in nasal cavity with transseptal access and crossing multiple incisions minimizes bleeding and reveals the tumor pedicle. Issue 3 (June 2020) - Omura, Kazuhiro; Nomura, Kazuhiro; Aoki, Satoshi; Hosokawa, Yu; Tanaka, Yasuhiro; Otori, Nobuyoshi; Kojima, Hiromi
Abstract: Objective: Sinonasal inverted papilloma can be resected endoscopically, but has a risk of recurrence. This risk can be minimized by identifying the pedicle of the tumor and ensuring complete resection. Intraoperative bleeding, particularly from the tumor, decreases endoscopic visualization and contributes to failure to identify the tumor pedicle, and piecemeal resection with dissection of the non-tumoral mucosa makes it impossible to distinguish the tumor pedicle. Previously reported transseptal access with crossing multiple incisions (TACMI) increases mobility of an inverted papilloma within the otherwise restricted nasal cavity. This technique often allows en bloc resection complete with the pedicle and control of bleeding. Methods: We retrospectively reviewed our patients who underwent endoscopic resection of inverted papilloma with or without TACMI and compared the operating times, estimated blood loss, and en bloc resection and recurrence rates between the two groups. Results: Thirty-five patients underwent endoscopic resection of inverted papilloma (Krouse stage 2–4) with ( n = 23) or without ( n = 12) TACMI. The operating time was longer in the TACMI group (218±68 min) than in the non-TACMI group (129±33 min). Estimated blood loss was less in the TACMI group (72±103 mL vs. 120±136.5 mL) but this finding was not significant. En bloc resection was achieved in 19 patients (83%) in the TACMI group but not in any patient in the non-TACMI group. There were no recurrences in the TACMI group. Multivariate analysis showed significant relationships between estimated amount of blood loss and operating time according to Krouse stage and whether or not TACMI was performed. Conclusions: Endoscopic resection of inverted papilloma with TACMI may achieve better treatment results with less blood loss.